Factors Affecting Clinical Outcome of Patients with Traumatic Brain Injury - Deepali Rishi Rajpal; Sachna Pramod Shetty; Manhar Shah (Asian Journal of Medical Research, 2020)
Background: The present study aims to describe the severity of injury [Glasgow Coma Scale (GCS)] and outcome of patients [Glasgow Outcome Scale (GOS)] who presented to our hospital with TBI and factors which affect the clinical outcome.Subjects and Methods:All patients, aged equal to or more than 18 years, presenting to the Emergency Department of our hospital due to head trauma during the study period were examined and assessed using GCS at the time of admission, and GOS at the time of discharge.Results:The most common mode of injury was road traffic accident (48%). At the time of admission, 47% had GCS of 13 to 15, 37% had GCS of 9 to 12 and 16% had GCS of 3 to 8. At the time of discharge, we found that 18 patients had GOS of 1, no patient had GOS of 2, 14 patients had GOS Of 3, 28 had GOS of 4 and 29 had GOS of 5. We found that age of the patients was significantly associated with the GOS severity (p value <0.05). Furthermore, GCS at admission was found to be significantly associated with GOS at discharge (p value <0.01). Midline shift on CT head, effaced basal cistern, and presence of subarachnoid haemorrhage were also found to be significantly associated with poor GOS at discharge.Conclusion: The results of our study may be used for stratification of patients, and developing prognostic models to improve the clinical outcome of head injury.